Boosting Memory by tDCS to Frontal or Parietal Brain Regions? A Study of the Enactment Effect Shows No Effects for Immediate and Delayed Recognition - Meier, Beat; Sauter, Philipp (Frontiers in Psychology, 2018)
Boosting memory with transcranial direct current stimulation (tDCS) seems to be an elegant way to optimize learning. Here we tested whether tDCS to the left dorsolateral prefrontal cortex or to the left posterior parietal cortex would boost recognition memory in general and/or particularly for action phrases enacted at study. During study, 48 young adults either read or enacted simple action phrases. Memory for the action phrases was assessed after a retention interval of 45 minutes and again after seven-days to investigate the long-term consequences of brain stimulation. The results showed a robust enactment effect in both test sessions. Moreover, the decrease in performance was more pronounced for reading than for enacting the phrases at study. However, tDCS did not reveal any effect on subsequent recognition memory performance. We conclude that memory benefits of tDCS are not easily replicated. In contrast, enactment at study reliably boosts subsequent memory.